Les énumérations testamentaires - Aude Argouse (Mélanges de la Casa de Velázquez, 2014)
Lists have something of a levelling effect. They place the objects they enumerate on the same conceptual plane. In the context of a colonial township in the Viceroyalty of Peru, Cajamarca, the compilation of lists of heirs by Indian testators appears to have been used by the Corregidor to allow Spaniards settled in what was legally a pueblo de indios to acquire a permanent right of residence and fight off impoverishment. This right was under permanent threat from the hostility of Franciscans and caciques alike. In a context of conflict by the pen, by placing debts payable, debts receivable and property side by side, lists of heirs blur the boundaries between persons, whether Indians or not, revealing a hierarchy of goods determined by the bonds of affection linking the testators with their heirs or assigns.